A single compartment simulation model of pharmacokinetics - Salankar, Harsh V.; Rode, Sonali B.; Bhavsar, Vinayak H. (International Journal of Basic & Clinical Pharmacology, 2018)
For better understanding about derivation of various parameters related to pharmacokinetics, this model is developed. Animals or human volunteers are not used in this model but the principles used in pharmacokinetic studies in volunteers are incorporated. There is detailed description about setting of the model and derivation of various parameters step by step. An example is followed to illustrate the calculations involved. Possibilities of further extension of model to derive additional parameters and variations are discussed. The experience indicates that the model serves as a good demonstration to undergraduate students and a meaningful experiment for PG-students for learning and as a practical-examination exercise. The purpose of the article is to widen the use of this simple teaching tool at various centers.